Species delimitation in Neotropical fishes of the genus Characidium (Teleostei, Characiformes) - Serrano, Erica A. [UNESP]; Melo, Bruno F. [UNESP]; Freitas-Souza, Diogo [UNESP]; Oliveira, Maria L. M. [UNESP]; Utsunomia, Ricardo [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Wiley-Blackwell, 2019)
Neotropical darters of the genus Characidium have a complex systematic history with several examples of sympatry throughout their distribution range in Neotropical freshwaters. Although various species within the genus have been used as models to investigate chromosomal evolution and biogeography, species boundaries and relationships still remain uncertain. Here, we use mitochondrial DNA sequences to perform species delimitation analyses within Characidium and test previous hypotheses of species richness within the Characidium zebra complex and among sympatric morphotypes of C. alipioi. Results indicate high genetic distances within tested species complexes and revealed the presence of strongly supported lineages such as the large C. lauroi group from southeastern Brazil. This suggests that the evolutionary history of these groups may be correlated with biogeographic history. Analyses also reveal that three geographically isolated populations of C. zebra represent a single species, leading us to reject prior hypothesis of multiple species. Species delimitation using mitochondrial data strongly supports the presence of two sympatric species within C. alipioi in southeastern Brazil despite limited morphological variation and conserved chromosomal patterns. These results provide a framework to further the study of systematics and evolution within Characidium.
Keywords: Crenuchidae; cytogenetics; DNA barcoding; freshwater fishes; sympatry